2001
DOI: 10.1002/1099-0690(200112)2001:23<4509::aid-ejoc4509>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Solvation Effects in Ethylmagnesium Bromide Addition to (2S)-O-(tert-Butyldimethylsilyl)lactal

Abstract: The diastereofacial selectivity of (2S)-O-(tert-butyldimethylsilyl)lactal towards nucleophilic addition of ethylmagnesium bromide is strongly solvent-dependent. We have shown that solute−solvent interactions occurring in a series of ethers, such as tetrahydrofuran, tetrahydropyran, diethyl ether, dipentyl ether, tert-butyl methyl ether, diisopropyl ether, diisopentyl ether, and anisole, can govern a diastereomeric switch from the anti to the syn isomer. Determination of the temper-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…As observed with di- tert -butyl ketone, treatment of fenchone with prenylmagnesium chloride at −78 °C and −40 °C resulted in little conversion (<5%) after 3 h. Addition at room temperature and at 66 °C, however, resulted in formation of the α-addition product 34 with high diastereoselectivity . As the temperature was increased, the diastereoselectivity decreased, but the regioselectivity did not change. , The exclusive formation of α-addition product 34 likely arises due to steric congestion in transition state 19 , similar to the addition of prenylmagnesium chloride to ketone 29 (Scheme ).…”
Section: Resultsmentioning
confidence: 97%
“…As observed with di- tert -butyl ketone, treatment of fenchone with prenylmagnesium chloride at −78 °C and −40 °C resulted in little conversion (<5%) after 3 h. Addition at room temperature and at 66 °C, however, resulted in formation of the α-addition product 34 with high diastereoselectivity . As the temperature was increased, the diastereoselectivity decreased, but the regioselectivity did not change. , The exclusive formation of α-addition product 34 likely arises due to steric congestion in transition state 19 , similar to the addition of prenylmagnesium chloride to ketone 29 (Scheme ).…”
Section: Resultsmentioning
confidence: 97%
“…Dynamic solvation effects have been observed by Cainelli and co-workers in the ethylmagnesium bromide addition to ( S )-2-( tert -butyldimethylsilyloxy)­propanal . The diastereofacial switch of selectivity syn/anti depends from the ethereal solvent and the temperature but with low diastereoselectivity levels.…”
Section: Stereodivergence In Acyclic Systemsmentioning
confidence: 91%
“…Dynamic solvation effects have been observed by Cainelli and co-workers in the ethylmagnesium bromide addition to (S)-2-(tert-butyldimethylsilyloxy)propanal. 19 The diastereofacial switch of selectivity syn/anti depends from the ethereal solvent and the temperature but with low diastereoselectivity levels. Addition of tertiary amines (5 mol %) to hexane for the addition of n-butyllithium to 2-phenylpropanal and to (S)-2-(tert-butyldimethylsilyloxy)propanal strongly influences syn/ anti ratios.…”
Section: Nucleophilic Additions To Carbonyl Compoundsmentioning
confidence: 99%
“…10). 26 We observed that solute-solvent interactions govern a diastereomeric switch from the anti to the syn isomer upon changing from THF to an anisole solvent system. In THF, the temperature scarcely affects the diastereofacial selectivity over a wide T range until T inv , after which the diastereomeric ratio (dr) rapidly decreases; the flattest part of the plot, and consequently the steady diastereomeric excess, is derived from a small value of DDH a , and thus the good diastereoselectivity can be entirely attributed to an entropic effect.…”
Section: Temperature Dependence Analyses Reveal Solvent Effectsmentioning
confidence: 98%